Generating political priority for skin cancer primary prevention: A case study from Aotearoa New Zealand. (17th October 2021) - Gage, Ryan; Leung, William; Gurtner, Marcus; Reeder, Anthony I.; McNoe, Bronwen M.; Signal, Louise
Abstract: Issues addressed: Skin cancer is highly prevalent but preventable, yet little research has been done on the challenges in generating political priority for skin cancer prevention. This qualitative study aimed to identify the political challenges to, facilitators of, and strategies to strengthen skin cancer prevention. The focus was on the case of Aotearoa New Zealand (NZ): a country with high skin cancer rates, but limited investment in primary prevention. Methods: Data sources included 18 national key informant interviews and documentary analysis. Data were analysed inductively for emerging themes and framed using a conceptual framework of political priority. Results: Challenges to advocates for skin cancer primary prevention include limited resources and competing priorities. Political‐level challenges include a lack of quick results compared with other initiatives vying for political attention, lack of negative externalities and, in NZ, misalignment with health system priorities. Challenges in the evidence base include the perceived conflict of sun protection with Vitamin D and physical activity, the lack of data on the financial burden of skin cancer and relatively low temperatures in NZ. Facilitators include strong policy community cohesion and issue framing, and weak opposition. Promising strategies to strengthen skin cancer prevention in NZ could include network building, using framing that resonates with policy makers and addressing key knowledge gaps in NZ, such as the financial burden of skin cancer. Conclusion: Advocacy for skin cancer prevention faces challenges due to advocates' limited resources, political challenges such as lack of quick results and gaps in evidence. Nonetheless, the initiative encounters little opposition and can be framed in ways that resonate with policy makers. So what?: Skin cancer is highly preventable, but advocates for prevention initiatives have struggled to gain political traction. This study identifies several strategies that could help raise the political profile for skin cancer prevention.